The development of a musically logical procedure for solving the problems of transcription for guitar performance of J.S. Bach's Suite in E Minor (BWV 996) - Bogle, James G. (My University, 1982)
The procedure that was developed involves the interrelationship of factors such as Baroque performance practice, Bach's keyboard orientation, Bach's compositional techniques, analysis of musical structure at various hierarchical levels, the delineation of structural units through performance variables, ornamentation, phrasing, articulation, fingering, expressive effect, and necessary compromises of the musical fabric to accommodate instrumental/technical limitations. A foundational premise of the procedure is that the guitarist should develop an idealized conception of the music and determine the manner in which to realize, or to most closely approximate, that conception on the instrument. This approach involves analysis, investigation of the interrelated factors, and extensive experimentation with the instrument to test alternative solutions. The study presents detailed discussions of both the process and results of such analysis, investigation, and experimentation.

An integral part of the professional training of the college level guitar performance major is the study and performance of the music of J.S. Bach. Because Bach did not compose any works for the guitar, the guitarist must perform transcriptions. Because of the insufficiency of published transcriptions of Bach's music that are adequate for use in the education of the college level guitar performance major, the study was designed to provide (1) a musically logical procedure for solving the problems of transcription for guitar performance, (2) a transcription of the Suiye in E minor that would be pedagogically adequate, and (3) a thorough basic introduction to ornamentation in Bach's music.
Keywords: Education, Music.